The Influence of Leadership Style, Work Culture and Work Environment on the Performance of Parepare City Employees - Ali, Rustan; Umar, Fahruddin; Nur, Irawati (Jurnal Ekonomi Balance, 2023)
The purpose of this research is to find out and analyze how much influence Leadership Style, Work Culture and Work Environment have on the Performance of Parepare City Employees. The analytical method used in this research is the method of observation, interviews, questionnaires and documentation, the sample determination method used is the saturated sampling method of 83 samples. The analysis method used is the multiple linear analysis method (multi linear regression). The results of the research show that partially influencing the performance of Parepare City Employees, Leadership Style (X1) with a calculated t value of 3.275 > t table 1.98896, a significant value of 0.000 < 0.05, as well as Work Culture (X2) partially influencing the value t count 4.005 > t-table 1.98896, significant value 0.000 < 0.05, but Work Environment (X3) has no effect and is not partially significant because the t count value is 0.605 < t table 1.98896, significant value 0.605 > 0, 05 on the Performance of Parepare City Employees.